Sustainable Procurement & Sustainable Distribution Influence the Organizational Performance (Economic, Social and Environmental): Moderating Role of Governance and Collaboration at Thai Food Industry - Kittisak Jermsittiparsert; Jutamat Sutduean; Chutipan Sutduean (International Journal of Supply Chain Management, 2019)
The prime goals of the current paper investigate the influence of SCM practices on organizational performance with moderating roles of ‘governor’ and ‘collaboration. The organizational performance was measured on the basis of three dimensions such as economic, social and environmental aspects. Data was collected from Thai food manufacturers and was tested visa Measurement Model and Structural Equation modeling. The study highlights influence of sustainable procurement and sustainable distribution or logistics to determine the organizational performance in Thai food industry. Moderating role of ‘governance’ and ‘collaboration’ were also examined and presented interesting outcomes. The research paper also focuses the need of considering various factors including business process, sustainability, collaboration, sustainable procurement, logistics or distribution with moderating role of governance and collaboration. Firms must strive for improving effectiveness of supply chain and organizational performance in highly competitive market.